Service quality, value, satisfaction and future intention in medical tourism - Abd Manaf, Noor Hazilah; Maulan, Suharni; Hussin, Husnayati; Jahn Kassim, Puteri Nemie; Alavi, Rokiah; Dahari, Zainurin (UiTM Press, Universiti Teknologi Mara., 2017)
Medical tourism is a new and exciting industry due to its rapid growth and huge economic potential. Malaysia is joining the bandwagon with Thailand, Singapore, and India in being the main medical tourist destination countries in Asia. Medical tourism is a term that is loosely used to denote patients who travel abroad to another country for medical treatment, which may range from wellness services to invasive procedures such as a heart bypass or organ transplant. As a major medical tourism country, the study seeks to explore the impact of service quality on perceived value, patient satisfaction, and future intention of patients to seek medical services in the country again. This study also investigates the relationship between patient satisfaction and perceived value; and between future intention and perceived value. A structural model by using PLS-SEM was established from the research finding with data collected from 161 responses from medical tourists surveyed in major destination hospitals in Kuala Lumpur, Malacca, and Penang.